De la raison vitale à la raison historique - Eve Giustiniani (Mélanges de la Casa de Velázquez, 2006)
Withdrawing from political activity in the wake of the crisis of 1917, Ortega y Gasset thereafter devoted himself to philosophy and an analysis of the crisis in Spain and Europe as a «crisis of Modern Times». The concept of vital reason, which he proposed to overcome the contradictions of modernity and pure reason, was worked out in the form of historical reason. The keystone of Ortega’s philosophical oeuvre, historical reason enabled him to reintroduce the notion of politics by associating crisis of reason, the disenchantment of reason and the decline of revolutionary utopianism. While justifying its practical decline theoretically, Ortega was convinced of its long-term cultural effects and devised a political programme as an extension of his programme of philosophical research. In the final analysis, then, Ortega’s proposition of vital and historical reason may be understood as the basis for a philosophical/political project.